A methodology for a global-local fatigue analysis of ancient riveted metallic bridges. Issue 3 (11th June 2018) - Leite, Regina C.G.; de Jesus, Abilio M.P.; Correia, José; Raposo, Patricia; Jorge, Renato N.; Parente, Marco Paulo; Calçada, Rui
Abstract : Purpose: Recent studies have proposed the application of local fatigue approaches based on fracture mechanics or on strain-life material relations for the fatigue analysis of metallic structures. However, only few studies in the literature apply local approaches in the riveted bridges analysis; although these approaches can be applied to any type of connections, requiring a detailed stress analysis of joints and, consequently, considerable computational resources costs. The approach based on S-N curves, formulated in nominal or net stresses, is more usual in the fatigue analysis of riveted bridges. Due to economic factors, riveted bridges have had their operating life extended, while changes in the transport system over the years have subjected such structures to overloads different from those originally planned. These bridges, most of them centenary, were not originally designed accounting for fatigue damage; they represent an important group of structures that are very likely subjected to significant fatigue damage indexes. These factors make necessary detailed residual fatigue life studies to substantiate the decisions of extend (or not) the operational period of these bridges. The paper aims to discuss these issues. Design/methodology/approach: The present paper presents a methodology aiming at applying the local approaches in the fatigue analysis of riveted joints of metallic bridges, through the use of sub-modeling techniques and procedures automation. The use of such techniques made such an application viable by keeping the computational costs involved at a moderate level. The proposed procedures were demonstrated using the Trezói Railway Bridge, located on the Beira Alta line, Portugal, built shortly after the Second World War. The proposed set of procedures allowed, through finite elements analysis, to obtain the relevant stresses to perform local fatigue damage analysis. A global structural model was constructed, using beam elements, and local models of a critical node were built with solid finite elements. The structure is analyzed under the passage of regulatory trains. The details of the modeling performed and the computation of the principal stresses in the vicinity of a node and the tangential/circumferential stresses at the holes of two critical riveted connections of that node are analyzed and a fatigue damage analysis is carried out. Findings: In the proposed submodelling approach, disassembling the complex riveted nodes into riveted subassemblies allowed the evaluation of the local stresses at riveted holes at an affordable computational cost. Originality/value: A methodology is proposed to allow the application of local fatigue analysis in real complex riveted joints, mitigating the computational costs that would result from a full model of the node with all rivets.